ANALISIS KINERJA PEGAWAI NEGERI SIPIL DALAM MENYELENGGARAKAN PELAYANAN PUBLIK PADA BADAN KEPEGAWAIAN, PENDIDIKAN DAN PELATIHAN DAERAH (BKDD) KABUPATEN SORONG - Pakpahan, Ratna Rosmauli; Ferdinandus, Arce Yulita; Muskita, Susana Magdalena Welly (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
The Regional Education and Training Personnel Agency (BKDD) is a government agency which has the task of carrying out the preparation and implementation of regional policies in the field of personnel and can be assigned to carry out the implementation of authority. The Sorong Regency Regional Education and Training Personnel Agency (BKDD) has four areas, namely the Performance Sector; Procurement Sector; Mutation Field and Training Field. However, in carrying out the duties and authority of the Sorong Regency Regional Education and Training Personnel Agency (BKDD), there are obstacles in providing public services. This research uses qualitative research methods using data collection steps and through observation, interviews and documentation. The results of this research are 1.) analysis of the performance of civil servants at the Sorong Regency Regional Personnel, Education and Training Agency (BKDD) in terms of Quality, Quantity, Implementation of Duties, Responsibility and Motivation, in general it has gone well. 2.) Analysis of Public Service for Civil Servants at the Sorong Regency Regional Personnel, Education and Training Agency (BKDD) seen from the principles of public service, namely: a. Public interest; b. Legal certainty; c. Equal Rights; d. Balance of Rights and Obligations and e. Professionalism; f. Participative; g. Non-Discriminatory; h. Openness; i. Accountability; j. Timeliness and k. Fast, easy and affordable, in general it has worked well.